2022
DOI: 10.1627/jpi.65.161
|View full text |Cite
|
Sign up to set email alerts
|

Cu/ZnO/Al<sub>2</sub>O<sub>3</sub>系触媒を用いたメタノールの酸化的改質による水素製造—Pdドープによる耐久性の向上と自己活性化能の発現—

Abstract: The autothermal reforming (ATR) of methanol was performed using the Cu/ZnO/Al2O3-based catalysts for the catalytic production of hydrogen. The Cu/ZnO/Al2O3 (CZA) catalyst exhibited a high hydrogen production rate during ATR even at a low external heating temperature of 100 °C. In the O2 on/off durability test, although the hydrogen production rate of CZA gradually decreased owing to copper aggregation, the Pd-doped Cu/ZnO/Al2O3 (Pd-CZA) catalyst maintained a high hydrogen production rate. The reduction tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In addition, the kinetic studies showed that the addition of palladium decreased the activation energy for steam reforming of methanol, which agrees well with our activity results. Nomoto et al [56] studied Cu and Pd-Cu catalysts in the autothermal reforming of methanol process after calcination and after reduction. In the case of the autothermal reforming (ATR) of methanol process carried out on the copper catalysts, only trace amount of hydrogen production was detected.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…In addition, the kinetic studies showed that the addition of palladium decreased the activation energy for steam reforming of methanol, which agrees well with our activity results. Nomoto et al [56] studied Cu and Pd-Cu catalysts in the autothermal reforming of methanol process after calcination and after reduction. In the case of the autothermal reforming (ATR) of methanol process carried out on the copper catalysts, only trace amount of hydrogen production was detected.…”
Section: Catalytic Activitymentioning
confidence: 99%